Structural and Affinity Analyses of G-Quadruplex DNA Aptamers for Camptothecin Derivatives - Naoki Sugimoto; Masayasu Kuwahara; Yuuya Kasahara; Shunsuke Kitadume; Hiroaki Ozaki; Yuri Imaizumi; Hiroto Fujita (MDPI AG, 2013)
We recently selected DNA aptamers that bind to camptothecin (CPT) and CPT derivatives from a 70-mer oligodeoxyribonucleotide (ODN) library using the Systematic Evolution of Ligands by EXponential enrichment (SELEX) method. The target-binding activity of the obtained 70-mer CPT-binding DNA aptamer, termed CA-70, which contains a 16-mer guanine (G)-core motif (G3TG3TG3T2G3) that forms a three-tiered G-quadruplex, was determined using fluorescence titration. In this study, truncated fragments of CA-70 that all have the G-core motif, CA-40, -20, -19, -18A, -18B, -17, and -16, were carefully analyzed. We found that CA-40 retained the target-binding activity, whereas CA-20, -19, and -18B exhibited little or no binding activities. Further, not only CA-18A but also the shorter length fragments CA-17 and -16 clearly retained the binding activity, indicating that tail strands of the G-quadruplex structure can significantly affect the target binding of G-quadruplex DNA aptamers. Further analyses using circular dichroism (CD) spectroscopy and fluorescence polarization (FP) assay were conducted to investigate the structure and affinity of G-quadruplex DNA aptamers.